A frequent hypofunctional IRAK2 variant is associated with reduced spontaneous hepatitis C virus clearance. Issue 5 (28th September 2015) - Wang, Hui; El Maadidi, Souhayla; Fischer, Janett; Grabski, Elena; Dickhöfer, Sabine; Klimosch, Sascha; Flannery, Sinead M.; Filomena, Angela; Wolz, Olaf‐Oliver; Schneiderhan‐Marra, Nicole; Löffler, Markus W.; Wiese, Manfred; et al.
<x xml:space="preserve">Abstract</x> Patients carrying very rare loss‐of‐function mutations in interleukin‐1 receptor–associated kinase 4 (IRAK4), a critical signaling mediator in Toll‐like receptor signaling, are severely immunodeficient, highlighting the paramount role of IRAK kinases in innate immunity. We discovered a comparatively frequent coding variant of the enigmatic human IRAK2, L392V (rs3844283), which is found homozygously in ∼15% of Caucasians, to be associated with a reduced ability to induce interferon‐alpha in primary human plasmacytoid dendritic cells in response to hepatitis C virus (HCV). Cytokine production in response to purified Toll‐like receptor agonists was also impaired. Additionally, rs3844283 was epidemiologically associated with a chronic course of HCV infection in two independent HCV cohorts and emerged as an independent predictor of chronic HCV disease. Mechanistically, IRAK2 L392V showed intact binding to, but impaired ubiquitination of, tumor necrosis factor receptor–associated factor 6, a vital step in signal transduction. Conclusion: Our study highlights IRAK2 and its genetic variants as critical factors and potentially novel biomarkers for human antiviral innate immunity. (Hepatology 2015;62:1375–1387)